Impact of Protein Binding Capacity and Daily Dosage of a Drug on Total Serum Bilirubin Levels in Susceptible Infants - Zon-Min Lee; Ling-Sai Chang; Kuang-Che Kuo; Meng-Chiao Lin; Hong-Ren Yu (MDPI AG, 2023)
Hyperbilirubinemia is a common pathological condition in neonates. Free bilirubin can penetrate the blood-brain barrier (BBB), which can lead to bilirubin neurotoxicity. In the context of predicting the risk of bilirubin neurotoxicity, although the specificity and sensitivity of free bilirubin levels are higher than those of total serum bilirubin (TSB), free bilirubin is not widely monitored in clinical practice. The threshold TSB levels at which phototherapy must be administered have been established previously. However, TSB levels are not well correlated with neurodevelopmental outcomes. Currently, TSB levels are commonly used to guide phototherapy for neonatal hyperbilirubinemia. Some clinical drugs can displace bilirubin from its albumin-binding sites, and consequently upregulate plasma bilirubin. Daily dosages play a vital role in regulating bilirubin levels. A drug with both a high protein binding capacity and high daily dosage significantly increases bilirubin levels in infants. Premature or very low birth weight (VLBW) infants are vulnerable to the upregulation of bilirubin levels as they exhibit the lowest reserve albumin levels and consequently the highest bilirubin toxicity index. Because bilirubin is involved in maintaining the balance between pro-oxidant and antioxidant agents, the downregulation of bilirubin levels is not always desirable. This review provides insights into the impact of protein binding capacity and daily dosage of drugs on the bilirubin levels in susceptible infants.